Beginning JSP , JSF and Tomcat Web Development From Novice to Professional - Zambon, Giulio; Sekler, Michael (Apress : Imprint: Apress, 2007)
Start building Java-based web applications now, even if you're a complete newcomer to Java. Comprehensive and example-driven, Beginning JSP™, JSF™, and Tomcat™ Web Development is all you need to develop dynamic web applications using JSP, connect to databases with JSF, and put them into action using the world's most popular open source Java web server, Apache Tomcat. A comprehensive introduction to JavaServer Pages (JSP), JavaServer Faces (JSF), and the Apache Tomcat web application server Key concepts made easy to grasp by numerous working examples and a walkthrough of the development of a complete e-commerce project Written for professionals by a practicing Java web application professional and expert.